The urgence of the code of conduct of the professional advocate in Indonesia - Alambara, Citra; Warka, Made; Suhartono, Slamet (Technium Social Sciences Journal, 2022)
This research is a normative legal research, namely research that focuses on the study or study of positive law. The Advocate profession is related to the task of serving the community to help solve the legal problems it faces. In carrying out their duties, advocates are guided by the Law on Advocates, but the norms of the law are considered insufficient, because the advocate profession is related to behavior that is not infrequently influenced by the moral ethics of advocates in every decision making. For this reason, in carrying out their duties, they still need an ethical guide as a guide in carrying out their professional duties. In this regard, the Advocate Professional Code of Ethics is very much needed in guiding the behavior of Advocates in making decisions and ethical behavior.